(untitled) (Bulletin KNOB, 2003)
This article focuses on the spatial structure, the street plan and the housing blocks of Friedrichstadt in Sleeswijk-Holstein. This ’ideal new town’ was founded in 1621 in the place where the rivers Treene and Eider flow together, by Remonstrants who had fled the Dutch Republic after the Synod of Dordrecht. Besides the town plan, as it is still to be traced back in the actual layout of the settlement, the underlying deed of foundation of Friedrichstadt has also been preserved. Freedom of religion for the future population played an important part in it. But much thought was also given to the spatial and administrative organisation of the new town, which was eventually executed according to plan. From analysis of the deed of foundation it appears that attention was paid to the defense of the town, but also to the characteristics of the future population. The question where and how they would have to live proves to have played a decisive role in the layout that Friedrichstadt would eventually get. By comparing the deed with the town plan it is evident that the extent of the various social groups and the place they were to be assigned within the establishment were approached thoughtfully. Spatial segregation played an important part in the views on this early 17th-century town establishment. In the end it all worked out differently. Friedrichstadt never developed into the superregional commercial settlement it was expected to become. Because an increase in population failed to take place, the fortress that the sovereign had promised to build was not realised either.